The validity and reliability of self-efficacy instrument for Islamic education teachers - Jaafar, Noornajihan (Opción, 2019)
This study aims to report the validity and reliability of the self-efficacy instrument for IEt (Institution of Engineering and Technology). A quantitative approach was used in this study, which 544 sets of questioners had been distributed to the IEt in several schools under the supervision of the Ministry of Education SMK. In result, with the loading factor 0.6, 4 factors were identified with the reliability value of student participation (0.844), classroom management (0.843), teaching strategies (0.814) and academic and character guidance (0.845) respectively. In conclusion, the validity and reliability gained has enabled the instrument to be adopted for the actual study.